2022
DOI: 10.7717/peerj.12873
|View full text |Cite
|
Sign up to set email alerts
|

A revision ofPlectanocotyle(Monogenea, Plectanocotylidae), with molecular barcoding of three species and the description of a new species from the streaked gurnardChelidonichthys lastovizaoff Algeria

Abstract: Background The family Plectanocotylidae includes parasites of the gills of marine fish; although nine genera and about 20 species have been described, almost no molecular information is available. Putting aside Plectanocotyle elliptica Diesing, 1850, supposedly a parasite of the white perch Morone americana, never found again since its original description, two species were valid within Plectanocotyle Diesing, 1850 before this work: Plectanocotyle gurnardi (Van Beneden & Hesse, 1863) Llewellyn, 1941 and Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“… Tunisia, W.M. Source Present study Present study; Ayadi et al (2022) Ayadi et al (2022) Ayadi et al (2022) Boudaya et al (2006) Body L. 1681 (1027–2427, n = 25) 2330 (1900–2800, n = 24) 2120 ± 350 (1100–3000, n = 31) 4020 (3380–4400, n = 5) 1841 (1500–2300, n = 11) Body W. 287 ± 90 (130–475, n = 32) 366 (250–430, n = 24) 310 ± 50 (200–430, n = 31) 472 (370–850, n = 5) 442 (210–600, n = 11) Oral suckers 51 ± 11 (30–70, n = 33) 41 (29–53, n = 21) 38 (30–46, n = 15) 60 (58–62, n = 4) 48 (40–60, n = 22) * × 43 ± 9 (28–64, n = 33) × 30 (20–73, n = 21) × 34 (25–45, n = 15) × 59 (55–62, n = 4) Pharynx 45 ± 10 (30–70, n = 32) 60 (50–77, n = 21) 48 (38–60, n = 15) 69 (68–70, n = 4) 45 (30–70, n = 24) * × 41 ± 9 (2–61, n = 32) × 56 (45–70, n = 21) × 42 (30–56, n = 15) × 69 (67–70, n = 4) Clamp 1 91 (51–115, n = 20) 94 (80–103, n = 10) × 82 (70–90, n = 8) 125 (90–180, n = 11) × 101 (35–135, n = 11 181 (175–195, n = 5) × 139 (125–160, n = 5) 137 (90–160, n = 17) × 110 (85–140, n = 17) × 80 (48–108, n = 20) ...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Tunisia, W.M. Source Present study Present study; Ayadi et al (2022) Ayadi et al (2022) Ayadi et al (2022) Boudaya et al (2006) Body L. 1681 (1027–2427, n = 25) 2330 (1900–2800, n = 24) 2120 ± 350 (1100–3000, n = 31) 4020 (3380–4400, n = 5) 1841 (1500–2300, n = 11) Body W. 287 ± 90 (130–475, n = 32) 366 (250–430, n = 24) 310 ± 50 (200–430, n = 31) 472 (370–850, n = 5) 442 (210–600, n = 11) Oral suckers 51 ± 11 (30–70, n = 33) 41 (29–53, n = 21) 38 (30–46, n = 15) 60 (58–62, n = 4) 48 (40–60, n = 22) * × 43 ± 9 (28–64, n = 33) × 30 (20–73, n = 21) × 34 (25–45, n = 15) × 59 (55–62, n = 4) Pharynx 45 ± 10 (30–70, n = 32) 60 (50–77, n = 21) 48 (38–60, n = 15) 69 (68–70, n = 4) 45 (30–70, n = 24) * × 41 ± 9 (2–61, n = 32) × 56 (45–70, n = 21) × 42 (30–56, n = 15) × 69 (67–70, n = 4) Clamp 1 91 (51–115, n = 20) 94 (80–103, n = 10) × 82 (70–90, n = 8) 125 (90–180, n = 11) × 101 (35–135, n = 11 181 (175–195, n = 5) × 139 (125–160, n = 5) 137 (90–160, n = 17) × 110 (85–140, n = 17) × 80 (48–108, n = 20) ...…”
Section: Resultsmentioning
confidence: 99%
“…In the taxonomy of Polyopisthocotylea, it is recurrent to distinguish species by the cox 1 divergence. Herein, in addition to the morphological differences, the four species of Plectanocotyle differ significantly by the divergence in their corresponding cox 1 sequences ( Table 3 ) especially given that the recent effort by Ayadi et al (2022) encompasses molecular data of thoroughly identified specimens (with complete traceability of host i.e., barcoded hosts and deposited hologenophores) of all currently known members of the genus except P. gurnardi which was completed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations